Relationship between students’ personality traits and their academic performance in history of education in tertiary institutions in Imo state, Nigeria - Alaribe, C. O.; Ipem, J. N.; Oyeyemi, A. A.; Chukwuonu, J. U. (Journal of Research in Adult and Continuing Education, 2023)
The focus of this study was to find out the relationship between students’ personality traits and their academic performance in History of Education in tertiary institutions in Imo State, Nigeria.Three research questions and three null hypotheses guided the study. Correlation research design was used in the study. The population for the study was 3100 which comprised 1030 students from Imo State University (IMSU) and 2070 students from Alvan Ikoku Federal College of Education (AIFCE). The study adopted simple random sampling technique.  A sample size of 180 students was drawn from AIFCE and 120 students from IMSU which summed up 300 respondents. An instrument titled Questionnaire on Personality Traits and Academic Performance of Students’ offering History of Education (QPTAPSHOE) was developed by the researchers for data collection. The instruments were face and content validated by three experts two from Educational Foundations and one from Measurement and Evaluation all in the Faculty of Education in UNN. The instrument was trial-tested on a sample of 20 students in UNN which is outside the study area which has the similar characteristics. The responses were subjected to Cronbach Alpha formula. The following reliability indices: 0.76, 0.89 and 0.74 were obtained for clusters A, B and C.  The reliability indices obtained showed that the questionnaire items were reliable. The three research questions were analyzed using Simple Linear Regression Analysis. One-way ANOVA was used to test the three null hypotheses at 0.05 level of significance. The overall result showed that personality traits in general have a low positive relationship with students’ academic performance offering History of Education in Imo State Tertiary Institution, Nigeria. The study recommends that government should ensure that only teachers with strong educational and History backgrounds are employed to teach History of Education to enhance students’ personality traits.
Keywords: History of Education; Personality Traits and Academic Performance